Cognitive Successive Interference Cancellation for Multi-User Visible Light Communication Systems - MARSUKI, AMINAH INDAHSARI; PAMUKTI, BRIAN (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
Wireless communication technology continues to face challenges in meeting high bandwidth demands and the capability to serve numerous users. One promising solution is the non-orthogonal multiple access (NOMA) scheme, particularly through the use of power domain (PD) in the application of visible light communication (VLC) technology. However, PD-NOMA still faces power allocation and detection issues at the receiver end. We propose the Cognitive-SIC-VLC method, which considers the line of sight (LOS). Using combined multiplexing techniques, variations in user positions within the system can result in low SNR (dB) values when detecting a BER threshold of 10-3. In three power allocation experiment scenarios, the third scenario was the best with an initial power allocation of 0.95 and a power increment for each user of 0.05. This has been proven to have very low SNR requirements for users close to the LED.